El Excentrico, 1958-09-05 - Garcia, Humberto:::Publisher:::::::::::: (San Jose, California; Garcia Printing, 2023)
September 5, 1958 [5 de septiembre de 1958]. Ano 9, No. 1. The cover contains photos of San Jose's former City Hall in the process of being demolished. The headline reads, "San Jose's City Hall - Historical Land Mark - Demolished."